Accommodating rising powers past, present, and future - Paul, T. V. (Cambridge : Cambridge University Press, 2016)
As the world enters the third decade of the twenty-first century, far-reaching changes are likely to occur. China, Russia, India, and Brazil, and perhaps others, are likely to emerge as contenders for global leadership roles. War as a system-changing mechanism is unimaginable, given that it would escalate into nuclear conflict and the destruction of the planet. It is therefore essential that policymakers in established as well as rising states devise strategies to allow transitions without resorting to war, but dominant theories of International Relations contend that major changes in the system are generally possible only through violent conflict. This volume asks whether peaceful accommodation of rising powers is possible in the changed international context, especially against the backdrop of intensified globalization. With the aid of historic cases, it argues that peaceful change is possible through effective long-term strategies on the part of both status quo and rising powers.
The Accommodation of Rising Powers in World Politics / T.V. Paul -- Realism, Balance of Power, and Power Transitions / Steven E. Lobell -- Globalization, Interdependence, and Major Power Accommodation / Philip Potter -- What Would E.H. Carr Say? : How International Institutions Address Peaceful Political Change / Krzysztof J. Pelc -- The Responsibility to Accommodate : Ideas and Change / Mlada Bukovansky -- Seizing the Day or Passing the Baton? : Power, Illusion, and the British Empire / Ali Zeren and John A. Hall -- The U.S. Accommodation of Communist China / Lorenz M. Lüthi -- Accommodation and Containment : Great Britain and Germany Prior to the Two World Wars / Martin Claar and Norrin M. Ripsman -- Did the U.S. and the Allies Fail to Accommodate Japan in the 1920s and the 1930s? / Jeffrey W. Taliaferro -- China's Bargaining Strategies for a Peaceful Accommodation after the Cold War / Kai He -- Partial Accommodation Without Conflict : India as a Rising Link Power / Aseema Sinha -- Brazil : Revising the Status Quo with Soft Power? / David R. Mares -- Prospects for the Accommodation of a Resurgent Russia / Nicola Contessi -- Great Power Accommodation and the Processes of International Politics / Theodore McLauchlin.
Title from publisher's bibliographic system (viewed on 08 Mar 2016).
Keywords: Middle powers; World politics -- 20th century; World politics -- 21st century; Middle powers -- Case studies; World politics -- 20th century -- Case studies; World politics -- 21st century -- Case studies